Assembly of the Thiolated [Au1Ag22(S‐Adm)12]3+ Superatom Complex into a Framework Material through Direct Linkage by SbF6− Anions. (11th March 2020) - Chen, Shuang; Du, Wenjun; Qin, Chenwanli; Liu, Danyu; Tang, Li; Liu, Ying; Wang, Shuxin; Zhu, Manzhou
Abstract: Building framework materials with desirable properties and enhanced functionalities with nanocluster/superatom complexes as building blocks remains a challenge in the field of nanomaterials. In this study, the chiral [Au1 Ag22 (S‐Adm)12 ] 3+ nanocluster/superatom complex (SC, in which S‐Adm=1‐adamantanethiol) was employed as a building block to construct the three‐dimensional (3D) superatom complex inorganic framework (SCIF) materials SCIF‐1 and SCIF‐2 through inorganic SbF6 − linkers. SCIF‐1 is racemic due to the assembly of two SC enantiomers in a single crystal. In SCIF‐2, the SC enantiomers are packed in separate crystals, thus producing larger channels and a circularly polarized luminescence (CPL) response. These two 3D SCIF materials exhibit unique sensitive photoluminescence (PL) in protic solvents. Our study provides a new pathway for creating novel open‐framework materials with superatom complexes and a foundation for the further development of 3D framework materials for sensing and other applications. Abstract : Ein frisches Gerüst : Eine neue Art von porösem Material, genannt SCIF (superatom complex inorganic framework), wurde durch Verknüpfung von Au1 Ag22 ‐Superatomclustern mit anorganischem SbF6 − aufgebaut. Die erhaltenen Materialien, SCIF‐1 und SCIF‐2, zeigen einzigartige Fluoreszenz‐ und CPL‐Eigenschaften.